Breathing at Birth: Neonatal Resuscitation in the Golden Minute of Life - Mohamed, Mossad Abdelhak Shaban; Abdelhalim, Abdelbaset Taher; Algantri, Khaled; Salam, Md Wasek; Taher, Salaheldin; Salam, Abdus (Bangladesh Journal of Medical Science, 2023)
At the time of delivery, the process of transition of the baby from the mother’s womb to the extra uterine environment is among the most complex adaptations that a human faces in different phases of life. This transition involves both physiological and anatomical changes in the baby that occurs in a relatively short span of time. While most babies can smoothly undergo this transition without much difficulty, there are indeed many who face difficulties in this complex phase resulting in perinatal asphyxia evident by delayed or absent crying, cyanosis, generalized hypotonia, and so on. An astute assessment is needed to identify these babies at birth who are at risk of death or severe complications in the future. After identification, prompt management and resuscitation should be started immediately after birth to ensure the survival of these babies. The first moments after birth are vital, and the first 60 seconds after delivery is known as the golden minute of life. In case a baby does need resuscitation, it is imperative that the baby gets identified and effective resuscitation starts in the golden minute of life. The longer resuscitation is delayed, the more the chance of death or future complications. This paper attempts to describe the steps of neonatal resuscitation of newborn babies suffering from perinatal asphyxia to help them establish effective breathing after birth. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 272-279